Incidence of zearalenone producing Fusarium species on sorghum grains - GUPTA, RAJNI (Indian Phytopathology, 2002)
287 isolates of Fusarium species (F. equiseti, F. moniliforme [Gibberella fujikuroi], F. oxysporum, F. semitectum [F. pallidoroseum], F. solani and F. sporotrichioides) were screened for zearalenone producing ability. Of these, 47 (out of 117), 54 (out of 118) and 18 (out of 52) isolates associated with pre-harvest, post-harvest and stored sorghum grains, respectively, were found to be zearalenone producers. These Fusarium species produced zearalenone in the range of 270 to 1800 ppb (pre-harvest grain), 240 to 1400 ppb (post-harvest grain) and 275 to 1160 ppb (stored grain).